Probing the whole ore chalcopyrite–bacteria interactions and jarosite biosynthesis by Raman and FTIR microspectroscopies - Adamou, Anastasia; Manos, Giorgos; Messios, Nicholas; Georgiou, Lazaros; Xydas, Constantinos; Varotsis, Constantinos (My University, 2016)
The whole ore chalcopyrite–bacteria interaction and the formation of the extracellular polymeric substances (EPS) during the bioleaching process by microorganisms found in the mine of Hellenic Copper Mines in Cyprus were investigated. Raman and FTIR microspectroscopies have been applied towards establishing a direct method for monitoring the formation of secondary minerals and the newly found vibrational marker bands were used to monitor the time evolution of the formation of covellite, and the K+ and NH4+-jarosites from the chalcopyrite surfaces. The Raman data indicate that the formation of K+-jarosite is followed by the formation of NH4+-jarosite. The variation in color in the FTIR imaging data and the observation of the amide I vibration at 1637 cm−1 indicate that the microorganisms are attached on the mineral surface and the changes in the frequency/intensity of the biofilm marker bands in the 900–1140 cm−1 frequency range with time demonstrate the existence of biofilm conformations.
Keywords: Bioleaching; Chalcopyrite; Extracellular polymeric substances (EPS); FTIR; K(+)- and NH(4)(+)-jarosites; Raman